Capn4 overexpression indicates poor prognosis of ovarian cancer patients - Yang, Ming-Fang (J Cancer, 2018)
Recent studies have shown a close correlation between Capn4 expression and the prognosis of patients with solid tumors. This study aimed to investigate clinical role of Capn4 in ovarian cancer. The expression of Capn4 in 113 ovarian cancer and 35 non-tumor tissue samples were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Capn4 expression was significantly upregulated in ovarian cancer tissues compared with non-tumor tissues (p < 0.01), and was positively correlated to FIGO stage, tumor grade and distant metastasis of ovarian cancer. Kaplan-Meier analysis indicated that patients with high Capn4 expression had shorter overall survival (HR = 1.929, 95%CI: 1.210-3.077, P= 0.006) and progress-free survival (PFS) (HR = 2.043, 95%CI: 1.276-3.271, P= 0.003). Moreover, univariate Cox regression analysis demonstrated that Capn4 overexpression was an unfavorable prognostic factor for ovarian cancer (HR = 2.819, 95%CI: 1.365-3.645, P = 0.003). After the adjustment with age, histological type and tumor size, multivariate Cox regression analysis showed that Capn4 expression level (HR = 2.157,95%CI: 1.091-3.138, P = 0.014), distant metastasis (HR = 1.576, 95%CI: 1.025-3.012, P = 0.028), tumor grade (HR = 1.408, 95%CI: 0.687-2.884, P = 0.037), and FIGO stage (HR = 1.791, 95%CI: 1.016-3.158, P=0.036) were independent poor prognostic indicators for ovarian cancer. In conclusion, Capn4 has the potential as a new prognostic marker for patients with ovarian cancer.